Cytotoxic CD4+ T-follicular cells may mediate killing against lymphoma cells - Xiao, Yin; Haeusl, Sigrun S.; Jethva, Gaurav; Weber, Johannes; Rosenwald, Andreas; Berberich-Siebelt, Friederike (Frontiers in Immunology, 2025)
Recently, we have identified CD4+PD-1+CXCR5+ T-follicular helper (TFH) cells with a distinct cytotoxic phenotype and named them “killer TFH (TFK)” cells. In this study, we aim to elucidate their presence and functional relevance in two different lymphoma subtypes, follicular lymphoma (FL) and diffuse large B-cell lymphoma (DLBCL). Flow cytometric analysis of tonsillar versus FL-cell suspensions revealed a heightened number of GZMK+NKG7/TIA-1+ TFK cells in the latter, accompanied by a significant increase in T-regulatory and T-follicular regulatory (TFR) cells. In contrast, DLBCL exhibited a decrease in TFH and TFR cell numbers, while concurrently demonstrating heightened frequencies of GZMK+TIA-1+ and especially GZMB+TIA-1+ TFK cells within the TFH population. Analysis of single-cell RNA sequencing data confirmed an origin-specific phenotype of TFK cells. Immunofluorescence staining of biopsy specimens detected CD4+BCL-6+TIA-1+ TFK cells within follicles and germinal centers (GC) in reactive lymph nodes and within their atypical counterparts in malignant lymph nodes. Their propensity to migrate into atypical GCs was more pronounced in higher grade FLs. Furthermore, the release of cytotoxic cargo by degranulation could be induced by stimulation of CD4+ cells in cultures of FL and DLBCL suspensions. In line, the direct cytotoxic capacity of TFK cells against lymphoma cells was demonstrated by killing assays with isolated cells, underscoring their potential as a prospective therapeutic target in lymphoma control.